Technology of physical training young footballers - Ніколаєнко Валерій Вадимович (Valery Nikolaenko) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to prove the technology of physical training of young players. Material and Methods: pedagogical observation and analysis of literature, both in the field of football, sports physiology and in the use of technologies that protect the health of the process of physical training of young athletes. Results: notes the need to review approaches to the organization of long-term preparation of sportsmen. It established the contradiction between the increasing demand for training of young sportsmen and features of the growing organism. Conclusion: the ways of rational construction of training process on the basis of the strategy of preparation of sports reserve and health at talented youth